(untitled) (Universal International Scientific Journal, 2026)
This article discusses the issues of further improving the education system in our republic. In particular, the formation of competencies in learners, the use of a competency-based approach in the educational process, and the importance of this approach in improving the quality of education, especially in technological education, are analyzed.